Circulating Small Extracellular Vesicles Profiling and Thrombin Generation as Potential Markers of Thrombotic Risk in Glioma Patients - Melnichnikova, Olga; Zhilenkova, Yulia; Sirotkina, Olga; Zolotova, Ekaterina; Pishchulov, Konstantin; Tastanbekov, Malik; Paltsev, Artem; Simakova, Maria (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Glioma patients (GM) are at high risk of venous thromboembolism (VTE). The role of microvesiculation in the cancer-associated thrombosis mechanisms has been previously demonstrated. The aim of this study was to evaluate the relative abundance of EVs and thrombin generation in combination with standard laboratory tests in patients with newly diagnosed GM as potential prognostic markers in VTE. Materials and methods: In the present study, 11 patients with newly diagnosed GM and 10 healthy volunteers were analyzed. EVs counting and their cellular origin (CytoFlex B4-R2-V2, Beckman Coulter, USA) and thrombin generation test (TGT, (Thrombinoscope BV, Netherlands) were performed. Results: In GM patients, the relative abundance of the of CD41+ EVs (platelet-derived) - and CD105+ EVs (endothelial-derived) were significantly higher than in the control group (44.3 [40.5; 52.4]% vs 27.2 [22.9; 31.0]%, p = 0.002, and 5.4 [4.8; 7.8]% vs 1.9 [1.5; 2.8]%, p = 0.0003, respectively). The D-dimer level was higher in GM patients compared to the control group (0.46 [0.38; 1.85] μg/ml FEU vs 0.36 [0.27; 0.40] μg/ml FEU, p = 0.03, respectively). There was a trend towards an increase in peak and rate thrombin formation in the GM group (p = 0.06). During the follow-up period, two patients (18%) developed thrombosis, had tumour size more than 5 cm, thrombocytopenia, increased VI and D-dimer. Conclusions: Analysis of platelet-derived EVs, platelet count, TGT in combination with D-dimer assessment could improve the stratification of patients prone to VTE, which needs to be confirmed in a larger sample.